Cytochrome c oxidase subunit 4 isoform 2-knockout mice show reduced enzyme activity, airway hyporeactivity, and lung pathology - Hüttemann, Maik; Bekeredjian, Raffi (The FASEB journal, 2012)
Cytochrome c oxidase (COX) is the terminal enzyme of the mitochondrial electron transport chain. The purpose of this study was to analyze the function of lung-specific cytochrome c oxidase subunit 4 isoform 2 (COX4i2) in vitro and in COX4i2-knockout mice in vivo. COX was isolated from cow lung and liver as control and functionally analyzed. COX4i2-knockout mice were generated and the effect of the gene knockout was determined, including COX activity, tissue energy levels, noninvasive and invasive lung function, and lung pathology. These studies were complemented by a comprehensive functional screen performed at the German Mouse Clinic (Neuherberg, Germany). We show that isolated cow lung COX containing COX4i2 is about twice as active (88 and 102% increased activity in the presence of allosteric activator ADP and inhibitor ATP, respectively) as liver COX, which lacks COX4i2. In COX4i2-knockout mice, lung COX activity and cellular ATP levels were significantly reduced (−50 and −29%, respectively). Knockout mice showed decreased airway responsiveness (60% reduced Penh and 58% reduced airway resistance upon challenge with 25 and 100 mg methacholine, respectively), and they developed a lung pathology deteriorating with age that included the appearance of Charcot-Leyden crystals. In addition, there was an interesting sex-specific phenotype, in which the knockout females showed reduced lean mass (−12%), reduced total oxygen consumption rate (−8%), improved glucose tolerance, and reduced grip force (−14%) compared to wild-type females. Our data suggest that high activity lung COX is a central determinant of airway function and is required for maximal airway responsiveness and healthy lung function. Since airway constriction requires energy, we propose a model in which reduced tissue ATP levels explain protection from airway hyperresponsiveness, i.e., absence of COX4i2 leads to reduced lung COX activity and ATP levels, which results in impaired airway constriction and thus reduced airway responsiveness; long-term lung pathology develops in the knockout mice due to impairment of energy-costly lung maintenance processes; and therefore, we propose mitochondrial oxidative phosphorylation as a novel target for the treatment of respiratory diseases, such as asthma.—Hüttemann, M., Lee, I., Gao, X., Pecina, P., Pecinova, A., Liu, J., Aras, S., Sommer, N., Sanderson, T. H., Tost, M., Neff, F., Aguilar-Pimentel, J. A., Becker, L., Naton, B., Rathkolb, B., Rozman, J., Favor, J., Hans, W., Prehn, C., Puk, O., Schrewe, A., Sun, M., Höfler, H., Adamski, J., Bekeredjian, R., Graw, J., Adler, T., Busch, D. H., Klingenspor, M., Klopstock, T., Ollert, M., Wolf, E., Fuchs, H., Gailus-Durner, V., Hrabě de Angelis, M., Weissmann, N., Doan, J. W., Bassett, D. J. P., Grossman, L. I. Cytochrome c oxidase subunit 4 isoform 2-knockout mice show reduced enzyme activity, airway hyporeactivity, and lung pathology.